Pemberdayaan Masyarakat Melalui Revitalisasi Fungsi Mushalla Sebagai Pusat Literasi Fikih Berbasis Partisipasi Komunitas Guna Meningkatkan Pemahaman dan Praktik Keagamaan Warga Dusun Bogem Desa Grogol Kecamatan Diwek Kabupaten Jombang - Baiq Tuhfatul Unsi; Izzatin Rofiqoh; Nasywa Ababiel (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The low level of fiqh literacy among rural communities and the suboptimal function of mushalla as centers of religious learning form the basis of this community service, which aims to improve the understanding and practice of religious activities through the revitalization of Mushalla Baitul Ma’mur as a community-based fiqh literacy center. This program employed a Participatory Action Research (PAR) approach consisting of planning, implementation, and participatory evaluation stages. The activities were carried out through the establishment of a Fiqh Literacy Corner and the implementation of regular study sessions using an intergenerational halaqah model involving 30 participants across 17 meetings. The results indicate a significant improvement in participants’ fiqh understanding, with an N-Gain score of 0.67 (moderate category) and 90% of participants showing learning improvement. Additionally, there was increased participation in discussions, greater independence in religious practices, and strengthened intergenerational social interaction. The intergenerational halaqah model proved effective in fostering participatory and contextual learning, while challenges such as resistance from certain participants were addressed through persuasive approaches and reinforcement of discussion norms. This program highlights the importance of optimizing mushalla as sustainable community-based religious literacy centers.